Biochemical characterization of a multi-drug resistant HIV-1 subtype AG reverse transcriptase: antagonism of AZT discrimination and excision pathways and sensitivity to RNase H inhibitors - Schneider, Anna; Buchholz, Bernd (Nucleic acids research, 2016)
We analyzed a multi-drug resistant (MR) HIV-1 reverse transcriptase (RT), subcloned from a patient-derived subtype CRF02_AG, harboring 45 amino acid exchanges, amongst them four thymidine analog mutations (TAMs) relevant for high-level AZT (azidothymidine) resistance by AZTMP excision (M41L, D67N, T215Y, K219E) as well as four substitutions of the AZTTP discrimination pathway (A62V, V75I, F116Y and Q151M). In addition, K65R, known to antagonize AZTMP excision in HIV-1 subtype B was present. Although MR-RT harbored the most significant amino acid exchanges T215Y and Q151M of each pathway, it exclusively used AZTTP discrimination, indicating that the two mechanisms are mutually exclusive and that the Q151M pathway is obviously preferred since it confers resistance to most nucleoside inhibitors. A derivative was created, additionally harboring the TAM K70R and the reversions M151Q as well as R65K since K65R antagonizes excision. MR-R65K-K70R-M151Q was competent of AZTMP excision, whereas other combinations thereof with only one or two exchanges still promoted discrimination. To tackle the multi-drug resistance problem, we tested if the MR-RTs could still be inhibited by RNase H inhibitors. All MR-RTs exhibited similar sensitivity toward RNase H inhibitors belonging to different inhibitor classes, indicating the importance of developing RNase H inhibitors further as anti-HIV drugs.